Dinamika Penyelenggaraan Pemerintahan Daerah di Provinsi Jawa Barat Pasca Terbitnya Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Wahyudin, M Yahya; Rahima, Syifa Nurul; Rosidin, Utang (SIYASI: Jurnal Trias Politica, 2025)
The implementation of Law Number 23 of 2014 concerning Regional Government has brought about fundamental changes in the structure of authority between the central government, provinces, and districts/cities. This study examines the dynamics of governance in West Java Province, with a focus on challenges, institutional responses, and intergovernmental synergy strategies. The results of the study indicate that West Java Province faces various problems, such as institutional unpreparedness, weak cross-government coordination, fiscal limitations, and fragmentation of information systems. Meanwhile, institutional responses indicate efforts to adjust structures and innovate public services, but have not been fully integrated with districts/cities. As a novelty, this study offers a strategic policy framework based on equitable asymmetric decentralization, including the formulation of regional capacity indicators, integration of planning information systems, and strengthening cross-regional collaboration. This research is expected to be a theoretical and practical contribution in formulating a model of regional governance that is adaptive and responsive to the local context.